PENGARUH MUSIK RELIGI TERHADAP PEMBENTUKAN AKHLAK SISWA MELALUI SENI MARAWIS: STUDI KASUS DI MTS AT-TAUFIQ CISURUPAN KABUPATEN GARUT - Maulida, Salma Nurul; Sandie Gunara; Jenuri (Jurnal An-Nufus, 2024)
This research explores the role of religious music media in forming morals through Marawis extracurricular activities at MTS At-Taufiq Cisurupan, Garut Regency. The research method used is qualitative with a case study approach. Data was obtained through participatory observation, in-depth interviews with resource persons (teachers) at the research locus. Analysis of research data uses content analysis techniques. Several research results show that religious music media called Marawis has a significant role in forming students' morals. Through practice, learning, and performance, students learn important values, such as discipline, cooperation, honesty, and perseverance. Religious music also helps them internalize the teachings of the Islamic religion and develop spiritual awareness. The implications of this research can be used as a basis for developing extracurricular programs in Islamic educational institutions.